Haemophilia specialist nurses’ perceptions of haemophilia B - Chaplin Steve; Birkedal Maj Friberg; Crilly Erica; Fletcher Simon; Garcia Sara; Mulders Greta; Myrin-Westesson Linda; Pollard Debra; Sanigorska Anna; Uitslager Nanda (The Journal of Haemophilia Practice, 2021)
Some clinicians believe that haemophilia B is associated with less bleeding than haemophilia A, yet there appears to be little difference in health-related outcomes. Current clinical practice reduces the risk of bleeds, making differences difficult to measure. We surveyed specialist haemophilia nurses to discern their opinions about the impact of haemophilia B compared to haemophilia A.